The New Stochastic Differential Equations Model for Controlling the Spread of Viral Diseases: HIV as an Example - kareem, Ahmed (ASJ - Academic Science Journal, 2025)
The main goal of presenting this manuscript is to study the dynamic activities of HIV spread and how to prevent it. The disease behavior was studied by proposing a new stochastic mathematical model. The solution's existence and uniqueness for the proposed mathematical model have been proven. We have also demonstrated the restrictions that must be met for society to rid itself of the scourge of the transmission of HIV by finding the basic reproduction rate. if the basic reproduction rate is less than one this means the disease-free point is stable. Conversely, if the basic reproduction rate is greater than one this means the disease - free point is unstable. The theoretical results were proven numerically through computer simulation using MATLAB.